Role of Lysosomal Acidification Dysfunction in Mesenchymal Stem Cell Senescence - Zhang, Weijun; Bai, Jinwu; Hang, Kai; Xu, Jianxiang; Zhou, Chengwei; Li, Lijun; Wang, Zhongxiang; Wang, Yibo; Wang, Kanbin; Xue, Deting (Frontiers in Cell and Developmental Biology, 2022)
Mesenchymal stem cell (MSC) transplantation has been widely used as a potential treatment for a variety of diseases. However, the contradiction between the low survival rate of transplanted cells and the beneficial therapeutic effects has affected its clinical use. Lysosomes as organelles at the center of cellular recycling and metabolic signaling, play essential roles in MSC homeostasis. In the first part of this review, we summarize the role of lysosomal acidification dysfunction in MSC senescence. In the second part, we summarize some of the potential strategies targeting lysosomal proteins to enhance the therapeutic effect of MSCs.